An insight into the functional genomics and species classification of Eudiplozoon nipponicum (Monogenea, Diplozoidae), a haematophagous parasite of the common carp Cyprinus carpio - Vorel, Jiří; Kmentová, Nikol; Hahn, Christoph; Bureš, Petr; Kašný, Martin (BMC genomics, 2023)
BACKGROUND: Monogenea (Platyhelminthes, Neodermata) are the most species-rich class within the Neodermata superclass of primarily fish parasites. Despite their economic and ecological importance, monogenean research tends to focus on their morphological, phylogenetic, and population characteristics, while comprehensive omics analyses aimed at describing functionally important molecules are few and far between. We present a molecular characterisation of monogenean representative Eudiplozoon nipponicum, an obligate haematophagous parasite infecting the gills of the common carp. We report its nuclear and mitochondrial genomes, present a functional annotation of protein molecules relevant to the molecular and biochemical aspect of physiological processes involved in interactions with the fish hosts, and re-examinate the taxonomic position of Eudiplozoon species within the Diplozoidae family. RESULTS: We have generated 50.81 Gbp of raw sequencing data (Illumina and Oxford Nanopore reads), bioinformatically processed, and de novo assembled them into a genome draft 0.94 Gbp long, consisting of 21,044 contigs (N50 = 87 kbp). The final assembly represents 57% of the estimated total genome size (~ 1.64 Gbp), whereby repetitive and low-complexity regions account for ~ 64% of the assembled length. In total, 36,626 predicted genes encode 33,031 proteins and homology-based annotation of protein-coding genes (PCGs) and proteins characterises 14,785 (44.76%) molecules. We have detected significant representation of functional proteins and known molecular functions. The numbers of peptidases and inhibitors (579 proteins), characterised GO terms (16,016 unique assigned GO terms), and identified KEGG Orthology (4,315 proteins) acting in 378 KEGG pathways demonstrate the variety of mechanisms by which the parasite interacts with hosts on a macromolecular level (immunomodulation, feeding, and development). Comparison between the newly assembled E. nipponicum mitochondrial genome (length of 17,038 bp) and other diplozoid monogeneans confirms the existence of two distinct Eudiplozoon species infecting different fish hosts: Cyprinus carpio and Carassius spp. CONCLUSIONS: Although the amount of sequencing data and characterised molecules of monogenean parasites has recently increased, a better insight into their molecular biology is needed. The E. nipponicum nuclear genome presented here, currently the largest described genome of any monogenean parasite, represents a milestone in the study of monogeneans and their molecules but further omics research is needed to understand these parasites' biological nature.
Keywords: genomika; Illumina; Parasites; kapři; Host–parasite interaction; Genome; paraziti; Carps; Sequencing; zvířata; Genomics; Annotation; Monogenea; fylogeneze; Trematoda; Mitochondrial genome; Helminths; Assembly; Nanopore; Phylogeny; Animals